Investigation of various soliton solutions to the Heisenberg ferromagnetic spin chain equation - Sulaiman, Tukur Abdulkadir; Aktuerk, Tolga; Bulut, Hasan; Baskonus, Haci Mehmet (Taylor & Francis Ltd, 2018)
This study uses two mathematical approaches in constructing dark, bright, kink-type and singular soliton solutions to the Heisenberg ferromagnetic spin chain equation. The (2+1)-dimensional Heisenberg ferromagnetic spin chain equation describes nonlinear dynamics of magnets. The acquired results in this study may help in explaining some physical meanings of some nonlinear physical models arising in electromagnetic waves. For instance, the hyperbolic tangent arises in the calculation of magnetic moment and rapidity of special relativity, the hyperbolic cotangent arises in the Langevin function for magnetic polarization. The 2-, 3-dimensional and the contour plots of all the acquired solutions are presented.
Keywords: The MEFM; SGEM; NLSEs; soliton solution